Provision and utilisation of health and nutrition services during COVID-19 pandemic in urban Bangladesh - Nguyen, Phuong Hong; Sununtnasuk, Celeste; Pant, Anjali; Tran, Lan Mai; Kachwaha, Shivani; Menon, Purnima (John Wiley & Sons, 2021)
The COVID-19 pandemic is expected to have profound effects on healthcare systems, but little evidence exists on service provision, utilisation, or adaptations. This study aimed to (1) examine the changes to health and nutrition service delivery and utilisation in urban Bangladesh during and after enforcement of COVID-19 restrictions and (2) identify adaptations and potential solutions to strengthen delivery and uptake. We conducted longitudinal surveys with health care providers (n = 45), pregnant women (n = 40), and mothers of children <2 years (n = 387) in February 2020 (in-person) and September 2020 (by phone). We used Wilcoxon matched-pairs signed-rank tests to compare the changes before and during the pandemic. Services delivery for women and children which require proximity were severely affected; weight and height measurements fell by 20–29 percentage points (pp) for pregnant women and 37–57 pp for children, and child immunisations fell by 38 pp. Declines in service utilisation were large, including drops in facility visitations (35 pp among pregnant women and 67 pp among mothers), health and nutrition counselling (up to 73 pp), child weight measurements (50 pp), and immunisations (61 pp). The primary method of adaptation was provision of services over phone (37% for antenatal care services, 44%–49% for counselling). Despite adaptations to service provision, continued availability of routine maternal and child health services did not translate into service utilisation. Further investments are needed to provide timely and accurate information on COVID-19 to the general public, improve COVID-19 training and provide incentives for health care providers and ensure availability of personal protective equipment for providers and beneficiaries.